Gender Representation in Directive Speech Acts of Teachers: A Study on Indonesian Language Learning in Automotive Vocational High Schools in Pasaman District - Putra, Ade Darma; Tressyalina, Tressyalina (JOLLT Journal of Languages and Language Teaching, 2024)
This study aims to examine gender representation in directive speech acts of Indonesian language teachers in Pasaman Regency Automotive Department Vocational Schools. Included in the type of qualitative research, this research applies descriptive analysis method. The research data is in the form of directive speech of male teachers and female teachers in Indonesian language learning at SMK Department of Automotive Pasaman Regency. It can be concluded that Indonesian teachers use various forms of directive speech acts, such as directions, orders, and instructions to students. Variants of the use of directive speech acts also show variations between male and female teachers, with three dominant variants commonly used by male teachers and five variants commonly used by female teachers. The results also reveal that female teachers tend to use the speech act of ordering or commanding as the dominant form, although they also show a sense of solidarity by using the speech acts of suggesting and advising. On the other hand, male teachers are more inclined to the direct approach and commanding without preamble. This difference reflects the complexity of the relationship between men’s and women’s language and thinking in the learning context.